Requirements for band-pass activation of Ca2+-sensitive proteins such as NFAT - Schoch, Arne; Pahle, Jürgen (Biophysical chemistry, 2019)
Several proteins are sensitive to frequency-modulated oscillations of calcium levels. Most of them exhibit increased activities for faster frequencies, a characteristic here referred to as high-pass activation. In contrast, the transcription factor NFAT is optimally activated at a specific frequency, a behaviour we call band-pass activation. We constructed a kinetic model of NFAT activation, confirming its ability for band-pass activation at experimentally observed frequencies. To characterise the requirements for band-pass activation further, we developed a minimal model, identifying antagonistic, calcium-dependent regulation with differently responsive regulators as essential for band-pass activation. Further, in optimisations cooperative binding proved to be an important feature for distinct frequency-decoding in models of high- and band-pass activation. A subsequent analysis of the optimised parameter sets revealed the most sensitive parameters along with additional preconditions for efficient decoding. Our analysis is not limited to NFAT, but potentially applies to any protein showing high- or band-pass activation.